Motives for reading and articulating user-generated restaurant reviews on Yelp.com. (12th August 2014) - Parikh, Anish; Behnke, Carl; Vorvoreanu, Mihaela; Almanza, Barbara; Nelson, Doug
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this research is to examine why and when restaurant consumers use and contribute user-generated reviews. This research is needed to determine the relevance of user-generated restaurant reviews in the current marketplace. Design/methodology/approach – The research methodology is based on a quantitative approach, and focused on current Yelp.com users as its population. Questions focused on the amount of usage, motives for usage, level of trust, users' tendencies to seek novelty in restaurants and motives for contribution. Findings – Users tend to trust the reviews on Yelp.com and engage in the community aspects of the platform. Yelp.com users also are altruistic in their motivation for contributing reviews to Yelp.com. Yelp.com users who access it tend to act on the information found within the reviews. Originality/value – Research articles have focused on user-generated reviews in the past; however, few have examined motivations of using and posting restaurant reviews. The value of conducting research comes from being able to understand the importance of user-generated restaurant reviews for customers in a comprehensive manner.